Effect of nanoclay on mechanical and thermal properties of kenaf recycle polyethylene wood plastic composites - Indok Nuratikah, Nizamudin (2017)
filler. Kenaf wood flour, rPE, MAPE and nanoclay were premixed manually and fed into single-screw extruder. Universal Tensile Machine (UTM) and Izod Impact were used to study the mechanical properties. Differential Scanning Calorimeter (DSC) and Thermal Gravimetric Analysis (TGA) were used to study the thermal properties. Scanning Electron Microscope (SEM) was used to observe the morphology. The effect of nanoclay on the mechanical properties, thermal properties and morphology were studied. Tensile strength of WrPC was decreased from 14.67 MPa to 14.07 MPa due to the agglomeration of nanoclay layer. Impact strength was increased from 6.07 kJ/m2 to 8.22 kJ/m2 due to the effectiveness distribution of applied stress to overcome the crack. Only one peak of glass transition temperature, Tg appeared at 133.5 °C as a result of miscible blending. Decomposition of WrPC was slightly affected by the addition of nanoclay. The internal structure of WrPC showed that the addition of nanoclay had filled the voids and lead to smooth morphology.